2011
DOI: 10.1088/1009-0630/13/5/02
|View full text |Cite
|
Sign up to set email alerts
|

Bohm Criterion in a Magnetized Plasma Sheath

Abstract: Bohm criterion in a magnetized plasma sheath is investigated with a fluid model.The upper and lower limits for the sheath criterion in different states of applied magnetic field are studied. The results from numerical simulation reveal that the magnetic field affects significantly the ion Mach number. The variation of the ion Mach number with the incident angle of the ions is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…But the new Bohm criterion corresponds to a misinterpretation of sheath model according to the mathematical structure of boundary layer when the non-neutrality parameter q → 0. According to Liu et al (2003); ; El Kaouini et al (2011); Ghomi and Khoramabadi (2011);Ji et al (2011);and Hatami and Shokri (2012), for an electropositive plasma in collisional regime (β → ∞), with cold ions and no ionizations (q c = q and q i → 0), the velocity of positive ions at the sheath edge (u 0 = v +s /c s ) must be bounded by: (3.20b) or in the pre-sheath representation:…”
Section: Misinterpreted Bohm Criterion For Plasmas In Collisional Regimementioning
confidence: 99%
See 2 more Smart Citations
“…But the new Bohm criterion corresponds to a misinterpretation of sheath model according to the mathematical structure of boundary layer when the non-neutrality parameter q → 0. According to Liu et al (2003); ; El Kaouini et al (2011); Ghomi and Khoramabadi (2011);Ji et al (2011);and Hatami and Shokri (2012), for an electropositive plasma in collisional regime (β → ∞), with cold ions and no ionizations (q c = q and q i → 0), the velocity of positive ions at the sheath edge (u 0 = v +s /c s ) must be bounded by: (3.20b) or in the pre-sheath representation:…”
Section: Misinterpreted Bohm Criterion For Plasmas In Collisional Regimementioning
confidence: 99%
“…But the new Bohm criterion corresponds to a misinterpretation of sheath model according to the mathematical structure of boundary layer when the non-neutrality parameter q → 0. According to Liu et al (2003); ; ; El Kaouini et al 2011; Ghomi and Khoramabadi (2011); Ji et al (2011); and Hatami and Shokri (2012), for an electropositive plasma in collisional regime (β → ∞), with cold ions and no ionizations (q c = q and q i → 0), the velocity of positive ions at the sheath edge (u 0 = v +s /c s ) must be bounded by: (3.20b) or in the pre-sheath representation: β, q) and η s = η (ξ s ; β, q) being the electric field at the sheath edge when q = 0. The problem is that to obtain these relations, the authors assume that the point S belongs to the exact solution when q = 0 and does not consider the dependence of η (orẏ) with the non-neutrality parameter q.…”
Section: Misinterpreted Bohm Criterion For Plasmas In Collisional Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Besides these, it is crucial in the understanding of the Earthʼs ionosphere [16] and astrophysical plasmas [17]. In the past few decades, many works have been devoted to the study of plasma-sheath characteristics with two or more populations of negatively charged particles (e.g., two groups of electrons, or those containing negative ions) and this is still an attractive subject in plasma physics [18][19][20][21][22]. Sheridan et al [10] experimentally observed the existence of two-temperature groups: hot and cold electrons in magnetron sputtering plasma.…”
Section: Introductionmentioning
confidence: 99%
“…They researched the effect of negative ions on sheath structure and Bohm criterion. We [19] studied the Bohm criterion in a magnetized plasma sheath taking collision into account, and presented the effects of an external magnetic field and the incident angle of the ions on Bohm criterion in 2011. In the same year, Ghomi [20] examined the effect of negative ion parameters on sheath formation criterion in electronegative plasmas without considering magnetic field.…”
Section: Introductionmentioning
confidence: 99%